Kewirausahaan Kaum Muda Daerah 3T (Terdepan-Terluar-Tertinggal) berbasis Ekologi dalam Minat dan Intensinya - Kristianto, Aloysius; Usman, Usman (Politeknik Negeri Ambon, 2020)
ABSTRACTThis research aims to find out the interests and intentions of young people in entrepreneurship in 3T areas in creating an ecology-based business by processing household organic waste into organic fertilizer as a product of the sale value in implementing sustainable development goals. The problem faced is how to foster interest and intentions of entrepreneurship among young people in border areas, household organic waste that is thrown away in vain, and high use of chemical fertilizers. The target of this research is young people in border areas with farmer family backgrounds not as entrepreneurs. This study uses participatory qualitative methods and project-based learning methods. The object of the research is purposefully selected using Focus Group Discussion (FGD) data collection techniques, unstructured open-ended interviews, participatory observation, and documentation.Â Factors that influence entrepreneurial interest are personality factors, sociological factors, and environmental factors as well as the processing of household waste into products of the sale value. The results of this study are that entrepreneurial interests and intentions are determined by freedom, self-efficacy, and more benefits if we are just employees, creativity. Ecologically-based business development has interesting potential to be developed, but in the production process, there is a tendency for these young people to be impatient (instant culture) in carrying it out and still lacking knowledge about how to package and market their products properly.Â